Fenomena Pejabat Kepala Daerah: Antara Kepentingan Publik dan Politik Lokal - Silva, Diego Dicky; Nadriana, Lenny; Santina, Rika (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2024)
This journal provides a comprehensive analysis of the appointment of acting regents and mayors, examining the intricate interplay between the imperatives of public interest and the dynamics of local politics. It conducts a thorough review of the legal frameworks governing the appointment process, encompassing relevant statutes, regulations, and judicial precedents. Furthermore, this study delves into the underlying motivations driving such appointments, including political affiliations, administrative considerations, and strategic alliances. Through a combination of qualitative and quantitative methods, including case studies and legal analyses, this research elucidates the multifaceted implications of acting appointments on governance structures, service delivery, and public perception. Moreover, it explores the challenges and opportunities for reforming the appointment process to enhance transparency, accountability, and the overall quality of local governance. By shedding light on these critical issues, this study contributes to a deeper understanding of the complexities inherent in the selection of acting regents and mayors, offering valuable insights for policymakers, legal practitioners, and scholars interested in advancing the principles of good governance at the local level.